Mengatasi Kesenjangan Epistemik Dakwah melalui Pendekatan Sosiologi: Model Intervensi Transformasional Berbasis Analisis Struktur–Agen dalam Konteks Fragmentasi Sosial Kontemporer: Overcoming Epistemic Gaps in Da'wah through a Sociological Approach: A Transformational Intervention Model Based on Structure-Agency Analysis in the Context of Contemporary Social Fragmentation - Moh. Rifqi Abdillah; Renisya Putri; Ali Hasan Siswanto (DIRASAH: Jurnal Kajian Islam, 2026)
This study is motivated by the epistemic gap that has emerged in contemporary da'wah practices, where the normative-textual approach has not been able to address the social complexities characterized by value fragmentation, identity polarization, and changes in social structures. The objectives of this study are (1) to identify forms of epistemic gaps in normative da'wah, (2) to explain why da'wah approaches have not optimally utilized sociological analysis tools, (3) to formulate the relevance of the sociological approach as an integrative methodology for reading the social problems of the ummah, and (4) to construct a transformational da'wah model based on structure-agency analysis. This study uses a qualitative-exploratory design with a critical and interpretive sociological approach. Data were collected through a comprehensive literature review of reputable articles, classical-contemporary sociological theories, and the latest da'wah research findings. Analysis was conducted using thematic analysis and a structure-agency interpretive framework to produce conceptual synthesis and operational models. The results of this study indicate that normative da'wah faces three major crises: a crisis in interpreting social reality, a methodological crisis in problem mapping, and a crisis of relevance in the context of digital society. The sociological approach has proven capable of providing powerful analytical tools for diagnosing the root causes of social problems and formulating da'wah interventions that are more responsive, empirical, and transformation-oriented. The conclusion of this study emphasizes the need for a new paradigm of da'wah that is diagnostic, contextual, and evidence-based, which is realized through a structural agent based transformational intervention model. This model not only strengthens theoretical contributions in the development of da'wah science and sociology, but also provides practical implications for the formulation of da'wah strategies that are relevant to contemporary social dynamics.